Effect of magnesium hydroxide nanoparticles with rod and plate shape on mechanical and biological properties of poly(L-lactide) composites - Kum, Chang Hun; Seo, Seong Ho; Kang, Sung Nam; Park, Bang Ju; Ahn, Dong June; Joung, Yoon Ki; Han, Dong Keun (SPRINGER, 2014)
Two kinds of magnesium hydroxide (Mg(OH)(2)) rods (Mg-Rod, 150 and 350 nm in size) and plates (Mg-PL, 60 and 300 nm) were prepared, and blended with poly(L-lactide) (PLLA) to obtain PLLA/Mg(OH)(2) composites to investigate the effect of the shape and size of Mg(OH)(2) particles. The structure, morphology, pH change, thermal and mechanical properties, cytotoxicity, and inflammation of Mg(OH)(2) control and PLLA/Mg(OH)(2) composites were evaluated. PLLA/Mg-Rod150 (30%) composite showed a 50% higher tensile strength and a 45% improved modulus as compared with PLLA/Mg-PL300 30% composite. Although Mg-Rods displayed similar cell viability (above 80%) as compared to Mg-PLs, the expression levels of TNF-alpha from Mg-PL60 gradually increased with increasing concentrations from 1 to 300 mu g. This indicates that Mg-PL60 had a potential cytotoxicity due to endocytosis. In addition, the byproduct of PLLA/Mg-Rods composite was more effectively neutralized than that of the PLLA/Mg-PLs composite, but cell viability and the expression levels of TNF-alpha were similar. Therefore, the use of our PLLA/Mg-Rod composite system would be a promising strategy to prevent the current fatal problems in biomedical applications including biodegradable implants such as stents.
Keywords: PARTICLE-SIZE; SCAFFOLDS; INFLAMMATION; POLYLACTIDE; POLYMER; DEGRADATION; MORPHOLOGY; ADHESION; BLENDS; STENT